BIBF1120 Protects against Diabetic Retinopathy through Neovascularization-Related Molecules and the MAPK Signaling Pathway - Xin Cao; Tao Li; Yongshen Tian; Yajing Tian; Chuang Gao; Dongmei Zhang; Yu Song (Journal of Ophthalmology)
Diabetic retinopathy (DR) is one of the microvascular complications of diabetes mellitus and a major pathological feature of neovascular DR. These patients potentially experience vision impairment and blindness. Platelet-derived growth factor receptor β (PDGFRβ), fibroblast growth factor receptor 1 (FGFR1), and vascular endothelial growth factor receptor 2 (VEGFR2) are implicated in the DR pathogenesis. Nintedanib (BIBF1120) is an oral selective dual receptor tyrosine kinase (RTK) inhibitor of VEGFR2, FGFR1, and PDGFRβ. In this study, intravitreal injection of BIBF1120 blocked the phosphorylation of VEGFR2, FGFR1, PDGFRβ, and MAPK signaling pathway proteins in a streptozotocin (STZ)-induced diabetic retinopathy mouse model. In in vitro cell experiments, BIBF1120 did not change cellular activity under normal conditions, while it further suppressed the tube formation, migration, and proliferation of high glucose-induced human retinal microvascular endothelial cells (HRMECs). Additionally, BIBF1120 blocked the phosphorylation of p38, JNK, and ERK1/2 in high glucose-treating HRMECs. Our results indicate that the BIBF1120 treatment can be a novel potential drug to protect against DR.